2007
DOI: 10.1111/j.1369-1600.2007.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

HUMAN GENETIC STUDY: Association analysis of genes encoding the nociceptin receptor (OPRL1) and its endogenous ligand (PNOC) with alcohol or illicit drug dependence

Abstract: Recent studies in animal models have shown that the nociceptin system, comprising nociceptin (or OFQ/N, encoded by PNOC) and the nociceptin receptor (an opioid receptor-like protein encoded by OPRL1), may be involved in alcohol and other drug reward pathways. To determine whether the nociceptin system is associated with alcohol or illicit drug dependence in humans, we analyzed 10 single nucleotide polymorphisms (SNPs) in OPRL1 and 15 SNPs in PNOC in a sample of 1923 European Americans from 219 multiplex alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 77 publications
0
33
0
6
Order By: Relevance
“…For example, Huang et al (2008) have reported a single-nucleotide polymorphism (SNP rs6010718) in the gene encoding the NOP receptor in alcohol-dependent individuals. In other studies, genetic variants of the OPRL1 gene were associated with opioid dependence (Xuei et al, 2008;Briant et al, 2010). In addition, increased vulnerability to alcohol dependence has been recently linked to DNA hypermethylation of the promoter regions of several genes, including the one encoding the NOP receptor suggesting the possibility that alcohol abuse is associated with a repressed NOP gene transcription (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…For example, Huang et al (2008) have reported a single-nucleotide polymorphism (SNP rs6010718) in the gene encoding the NOP receptor in alcohol-dependent individuals. In other studies, genetic variants of the OPRL1 gene were associated with opioid dependence (Xuei et al, 2008;Briant et al, 2010). In addition, increased vulnerability to alcohol dependence has been recently linked to DNA hypermethylation of the promoter regions of several genes, including the one encoding the NOP receptor suggesting the possibility that alcohol abuse is associated with a repressed NOP gene transcription (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, SNPs within the NKAIN2 gene showed evidence of an association with neuroticism [50]. The OPRL1 gene encodes a G-protein-coupled receptor and may be involved in the regulation of numerous brain activities, particularly instinctive and emotional behaviors [51,52]. In addition, SNPs in the OPRL1 locus were associated with both alcohol and opioid dependence [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Two adjacent SNPs in intron 1 of OPRL1 were marginally associated with opioid dependence (rs6512305 (p=0.05), and rs6090043 (p=0.05)). However, neither gene showed association with both alcohol and opioid dependence (12).…”
Section: Xuei Et Al (2008) Conducted a Study On The Role Of The Nocmentioning
confidence: 88%
“…Seven studies investigated the role of genes in the opioid system (11)(12)(13)(14)(15)(16)(17)(18). Genes encoding all three types of opioid receptors were studied with variable results.…”
Section: Opioid Systemmentioning
confidence: 99%